Interleukin‐10 promoter polymorphisms and haplotypes in patients with Guillain–Barré syndrome - Shoma Hayat; Asaduzzaman Asad; Moriam Akter Munni; Md. Abu Jaher Nayeem; Md. Golam Mostafa; Israt Jahan; Md. Zakir Hossain Howlader; Quazi Deen Mohammad; Zhahirul Islam (Annals of Clinical and Translational Neurology, 2024)
Abstract Objective Interleukin‐10 (IL‐10) is a multifunctional cytokine that exerts both pro‐ and anti‐inflammatory effects on the immune system as well as in the pathogenesis of Guillain–Barré syndrome (GBS). We investigated whether the three common polymorphisms ‐1082 G/A(rs1800896), ‐819 C/T(rs1800871), and ‐592 C/A(rs1800872) in the promoter region of IL‐10 have any influence on the susceptibility, severity, and clinical outcome of GBS. Methods IL‐10 promoter polymorphisms were investigated in 152 patients with GBS and 152 healthy controls from Bangladesh using polymerase chain reaction and restriction fragment length polymorphism (PCR‐RFLP), and allele‐specific oligonucleotide‐PCR (ASO‐PCR). Haplotype patterns and frequencies were analyzed using Heatmaply R‐package, chi‐square, and Fisher's exact test. The serum level of IL‐10 was measured through enzyme‐linked immunosorbent assays. p‐values < 0.05 were considered statistically significant. Results IL‐10 promoter polymorphisms ‐1082 G/A, ‐819 C/T, and ‐592 C/A were not associated with GBS susceptibility. The homozygous ‐819 TT genotype showed a tendency with susceptibility (p = 0.029; pc = 0.08) and was prevalent in axonal variants of GBS compared to demyelinating subtypes and controls (p = 0.042, OR = 8.67, 95% CI = 1.03–72.97; pc = 0.123 and p = 0.005, OR = 4.2, 95% CI = 1.55–11.40; pc = 0.015, respectively). Haplotype analysis revealed 19 patterns of genotypes and high IL‐10 expression haplotype combinations (GCC/GTA, GCC/ATA, and GCC/GCA) may have influence on disease severity (p = 0.026; pc = 0.078). Serum expression of IL‐10 was elevated in GBS patients ([GBS, 12.16 ± 45.71] vs. [HC, 0.65 ± 5.17] pg/mL; p = 0.0027) and varied with disease severity ([severe‐GBS, 15.25 ± 51.72] vs. [mild‐GBS, 3.59 ± 19.79] pg/mL, p = 0.046). Interpretation The ‐819 TT genotypes influence axonal GBS, and high frequency of IL‐10 expression haplotype combination with elevated serum IL‐10 may play an important role in disease severity.